Partial purification and functional characterization of Ts19 Frag-I, a novel toxin from Tityus serrulatus scorpion venom - Priscila C. Lima; Karla C. F. Bordon; Manuela B. Pucca; Felipe A. Cerni; Karina F. Zoccal; Lucia H. Faccioli; Eliane C. Arantes (Journal of Venomous Animals and Toxins including Tropical Diseases, 2015)
Abstract Background The yellow scorpion Tityus serrulatus (Ts) is responsible for the highest number of accidents and the most severe scorpion envenoming in Brazil. Although its venom has been studied since the 1950s, it presents a number of orphan peptides that have not been studied so far. The objective of our research was to isolate and identify the components present in the fractions VIIIA and VIIIB of Ts venom, in order to search for a novel toxin. The major isolated toxins were further investigated for macrophage modulation. Methods The fractions VIIIA and VIIIB, obtained from Ts venom cation exchange chromatography, were rechromatographed on a C18 column (4.6 × 250 mm) followed by a reversed-phase chromatography using another C18 column (2.1 × 250 mm). The main eluted peaks were analyzed by MALDI-TOF and Edman’s degradation and tested on macrophages. Results The previously described toxins Ts2, Ts3-KS, Ts4, Ts8, Ts8 propeptide, Ts19 Frag-II and the novel peptide Ts19 Frag-I were isolated from the fractions VIIIA and VIIIB. Ts19 Frag-I, presenting 58 amino acid residues, a mass of 6,575 Da and a theoretical pI of 8.57, shares high sequence identity with potassium channel toxins (KTx). The toxins Ts4, Ts3-KS and the partially purified Ts19 Frag-I did not produce cytotoxic effects on macrophage murine cells line (J774.1). On the other hand, Ts19 Frag-I induced the release of nitric oxide (NO) by macrophages, while Ts4 and Ts3-KS did not affect the NO production at the tested concentration (50 μg/mL). At the same concentration, Ts19 Frag-I and Ts3-KS increased the production of interleukin-6 (IL-6). Ts19 Frag-I and Ts4 did not induce the release of IL-10, IL-1β or tumor necrosis factor-α by macrophage cells using the tested concentration (50 μg/mL). Conclusions We partially purified and determined the complete sequence and chemical/physical parameters of a new β-KTx, denominated Ts19 Frag-I. The toxins Ts4, Ts3-KS and Ts19 Frag-I showed no cytotoxicity toward macrophages and induced IL-6 release. Ts19 Frag-I ...